(untitled) (International Journal of Food and Nutritional Sciences, 2019)
This comprehensive review explores the imperative role of employability skills in modern workplaces, analyzing diverse literature to elucidate their necessity and adoption. In the face of rapid technological advancements, organizational shifts, and globalization, individuals must cultivate a versatile skill set to thrive. The review emphasizes the critical importance of adaptability to technological change, effective teamwork, global competence, prioritization of soft skills, and a commitment to lifelong learning. The evolving professional landscape demands that employees actively learn and adopt these skills to remain competitive, contribute meaningfully to organizations, and navigate the complexities of contemporary work environments. As workplaces continue to evolve, the acquisition of employability skills emerges as a linchpin for personal and professional success, reflecting a paradigm shift in the skills landscape of the Fourth Industrial Revolution.